Impact of the COVID-19 pandemic waves on adults with moderate-to-severe atopic dermatitis in the Dutch general population: a population-based longitudinal cohort study - Chen, Rui; Loman, Laura; Postmus, Douwe; Schuttelaar, Marie L. A. (Frontiers in Public Health, 2025)
BackgroundThis study aimed to investigate the impact of COVID-19 waves on mental health, pandemic-related wellbeing, and social functioning in adults with moderate-to-severe atopic dermatitis (AD) and without AD in the Dutch general population.MethodsBetween 2020 and 2022, 31 COVID-19 questionnaires (COVQs) were sent to 140,145 Lifelines adult participants, collecting data on mental health [major depression disorder (MDD), generalized anxiety disorder (GAD)], pandemic-related wellbeing [COVID-19-related concerns, quality of life (QoL)], and social functioning (loneliness, social relations). AD information was collected through a digital questionnaire sent to all Lifelines adults in 2020. Data were divided into three waves according to the COVID-19 timeline in the Netherlands: March–June 2020 (wave 1); July 2020–June 2021 (wave 2); July 2021–October 2022 (wave 3). Generalized linear mixed models were performed for each outcome.ResultsIn total, 49,216 participants with 790,936 completed COVQs were included. Compared with wave 1, almost all health-related outcomes, including the prevalence of MDD and GAD, COVID-19-related concerns, loneliness, and QoL, had returned to similar levels by wave 3 in the overall population, while social relations remained impaired. Furthermore, participants with moderate-to-severe AD, women, young adults (18–29 years), and those with a history of mental health problems showed worse health-related outcomes than their counterparts.ConclusionBoth participants with and without moderate-to-severe AD showed partial recovery in mental health and wellbeing by the third COVID-19 wave; however, social relations remained impaired. Individual with moderate-to-severe AD, women, younger adults, and those with pre-existing mental health problems were more affected overall. Future studies should focus on developing strategies to improve social connectedness, and vulnerable groups warrant continued attention.